2009
DOI: 10.1161/hypertensionaha.108.127670
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α–Converting Enzyme Is a Key Regulator of Agonist-Induced Cardiac Hypertrophy and Fibrosis

Abstract: Abstract-Cardiac remodeling is associated with hypertrophy and fibrosis processes, which may depend on the activity of matrix metalloproteinases (MMPs) and "a disintegrin and metalloproteinases" (ADAMs). We investigated whether ADAM-17 (tumor necrosis factor-␣-converting enzyme [TACE]) plays a role in agonist-induced cardiac remodeling and the relationships established among TACE, MMP-2, and ADAM-12. We targeted TACE in rodent models of spontaneous and agonist-induced hypertension using RNA interference combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 29 publications
3
85
0
Order By: Relevance
“…ADAM12 expression is also markedly up-regulated in cancers of the liver, lung, stomach, colon, prostate, bladder, and in glioblastoma (13)(14)(15)(16)(17)(18). Increased ADAM12 expression levels are found in the cardiac tissue of patients with hypertrophic obstructive cardiomyopathy (19) and in mice with angiotensin II-induced hypertension and cardiac hypertrophy (20,21). During inflammatory responses and aseptic osteolysis associated with loosened hip replacement implants, ADAM12 is up-regulated in the interface tissue around loosening implants (22).…”
mentioning
confidence: 99%
“…ADAM12 expression is also markedly up-regulated in cancers of the liver, lung, stomach, colon, prostate, bladder, and in glioblastoma (13)(14)(15)(16)(17)(18). Increased ADAM12 expression levels are found in the cardiac tissue of patients with hypertrophic obstructive cardiomyopathy (19) and in mice with angiotensin II-induced hypertension and cardiac hypertrophy (20,21). During inflammatory responses and aseptic osteolysis associated with loosened hip replacement implants, ADAM12 is up-regulated in the interface tissue around loosening implants (22).…”
mentioning
confidence: 99%
“…We have identified MMP-2, MMP-7, ADAM-12 and ADAM-17/TACE as mediators of angiotensin II-induced hypertensive cardiac disease. We have also found that gene expression of these metalloproteinases changes throughout disease development [16,36,[40][41][42]. Moreover, some MMPs and ADAMs (such as MMP-7 and ADAM-17) appear to regulate others (such as MMP-2 and ADAM-12).…”
Section: Gpcr Signaling Through Mmps and Adams: A Clock For Disease Dmentioning
confidence: 69%
“…In addition to the transient expression of individual MMPs and ADAMs, we observe the emergence of a novel specialization of functions: MMP-7 and MMP-2 may regulate vascular tone whereas ADAM-17 and ADAM-12 may signal cardiac hypertrophy and fibrosis under transcriptional control of MMP-7 and ADAM-17. This functional specialization is determined by temporal differences in expression and hierarchical relationships among MMPs and ADAMs [16,36,[40][41][42].…”
Section: Gpcr Signaling Through Mmps and Adams: A Clock For Disease Dmentioning
confidence: 99%
“…Research using experimental animal models of agonist-induced and spontaneous hypertension suggests that MMPs and ADAMs might regulate one another through transcriptional mechanisms to mediate pro-hypertensive, pro-hypertrophic and pro-fibrotic responses to GqPCR agonists [31,55,56]. Therefore, different MMPs and ADAMs probably contribute to disease development within different time windows through overlapping mechanisms and substrates.…”
Section: Resultsmentioning
confidence: 99%